p53, stem cell biology and childhood blastomas - Oh, Lixian; Hafsi, Hind; Hainaut, Pierre; Ariffin, Hany (Lippincott, Williams & Wilkins, 2019)
Purpose of reviewChildhood blastomas, unlike adult cancers, originate from developing organs in which molecular and cellular features exhibit differentiation arrest and embryonic characteristics. Conventional cancer therapies, which rely on the generalized cytotoxic effect on rapidly dividing cells, may damage delicate organs in young children, leading to multiple late effects. Deep understanding of the biology of embryonal cancers is crucial in reshaping the cancer treatment paradigm for children.Recent findingsp53 plays a major physiological role in embryonic development, by controlling cell proliferation, differentiation and responses to cellular stress. Tumor suppressor function of p53 is commonly lost in adult cancers through genetic alterations. However, both somatic and germline p53 mutations are rare in childhood blastomas, suggesting that in these cancers, p53 may be inactivated through other mechanisms than mutation. In this review, we summarize current knowledge about p53 pathway inactivation in childhood blastomas (specifically neuroblastoma, retinoblastoma and Wilms' tumor) through various upstream mechanisms. Laboratory evidence and clinical trials of targeted therapies specific to exploiting p53 upstream regulators are discussed.SummaryDespite the low rate of inherent TP53 mutations, p53 pathway inactivation is a common denominator in childhood blastomas. Exploiting p53 and its regulators is likely to translate into more effective targeted therapies with minimal late effects for children. (see Video Abstract, Supplemental Digital Content 1, http://links.lww.com/COON/A23). © 2019 Wolters Kluwer Health, Inc. All rights reserved.